95 Anniversary of Marianna Sankiewicz-Budzynski - of Audioengineering Society, Polish Section (Archives of Acoustics, 2017)
On September 23, 2016, we celebrated the 95 anniversary of Marianna Sankiewicz-Budzynski (more information at http://mariannasankiewicz.pl/).